2023
DOI: 10.14710/dijb.6.1.2023.50-56
|View full text |Cite
|
Sign up to set email alerts
|

Green credit and bank performance in Indonesia

Sri Andaiyani,
Fida Muthia,
Agil Novriansa

Abstract: A new challenge for the banking sector In Indonesia is integrating social aspects in firm performance reports. Green Credit is expected to substantially drive capital allocation to sustainable development which eventually will impact the pattern of production and consumption in the future. In this study, using commercial bank data in Indonesia, we estimate an empirical model of the effect of green credit on bank performance in Indonesia during the period 2015 to 2021. We employ a panel dynamic model using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…This finding contrasts with the research conducted by Andaiyani et al (2023), using a population and sample of various banks in Indonesia, which found that green credit has no impact on bank profitability in terms of return on assets. In this research, which includes a larger number of banks in Indonesia, we found that green credit indeed affects return on assets but in a negative manner.…”
Section: The Influence Of Green Credit On Bank Profitabilitycontrasting
confidence: 99%
“…This finding contrasts with the research conducted by Andaiyani et al (2023), using a population and sample of various banks in Indonesia, which found that green credit has no impact on bank profitability in terms of return on assets. In this research, which includes a larger number of banks in Indonesia, we found that green credit indeed affects return on assets but in a negative manner.…”
Section: The Influence Of Green Credit On Bank Profitabilitycontrasting
confidence: 99%